Bionomics of Aedes aegypti subpopulations (Diptera: Culicidae) from Misiones Province, northeastern Argentina - Tejerina, Edmundo Fabricio (2009)
Life statistics of four Aedes aegypti subpopulations from the subtropical province of Misiones were studied during autumn and winter, under semi-natural conditions, coming from the localities of Posadas (SW), San Javier (SE), Bernardo de Irigoyen (NE) and Puerto Libertad (NW). The eastern subpopulations are geographically separated by the central mountain system of the province from the western subpopulations. High percentages of larval and pupal survival (97-100%) were recorded, and no significant differences were detected among the four subpopulations. Larvae and pupae lasted approximately 8 days to complete their development, no significant differences being detected among the four subpopulations studied. Sex ratio recorded did not differ significantly from 1:1. Male longevity did not show difference among the different subpopulations, but female longevity was remarkably different among the four subpopulations (F = 16.27; d.f. = (3;8); P = 0.0009), ranging among 11.45 days for San Javier and 57.87 days for Posadas. Fecundity also varied considerably among subpopulations, the greatest number (307.44 eggs/female) being recorded for Posadas (F = 4.13; d.f. = (3;8); P = 0.04). Ae. aegypti females of the western subpopulations lived longer than the eastern subpopulations studied, therefore, the risk of dengue outbreak would be greater on the Misiones Province border with Paraguay.